Three-Dimensional Kinematic Analysis of the Lower Extremity in Ruesi Dat Ton Postures Performed by Healthy Volunteers - Ketmanee Jongjiamdee; Thanaphak Chaowpeerapong; Pichitpol Kerdsomnuek; Suksalin Booranasubkajorn; Bavornrat Vanadurongwan; Weerawat Limroongreungrat; Pravit Akarasereenont; Apichat Asavamongkolkul (Tehran University of Medical Sciences, 2023)
This study was conducted to investigate the three-dimensional (3D) joint angles and muscle activities of the lower extremities when performing the Ruesi Dat Ton: a form of traditional Thai medicine involving stretching and strengthening postures. Thirty healthy volunteers were recruited in order to let them perform five Ruesi Dat Ton postures, namely Tha Kae Khao Kae Kha, Tha Kae Lom Nai Ook Nai Eo, Tha Kae Klon Pattakhat, Tha Kae Siat Ook, and Tha Kae Lom Pat-Khat Kae Lom Nai Eo, by a random sequence of postures. The 3D joint angles and muscle activities during the performance of the Ruesi Dat Ton were analyzed at the 3D-motion analysis laboratory. Descriptive statistics were used for the analysis. All the Ruesi Dat Ton postures were in the normal range of motion of the back, hips, knees, and ankles. However, when compared to the joint angle values from the 3D motion analysis, a higher joint angle was found in the hip rotation of Tha Kae Khao Kae Kha (27.99±16.72 degrees), Tha Kae Lom Nai Ook Nai Eo (25.99±14.76 degrees), and Tha Kae Klon Pattakhat (20.99±12.59 degrees), knee flexion of Tha Kae Siat Ook (140.05±8.98 degrees), and trunk flexion of Tha Kae Lom Pat-Khat Kae Lom Nai Eo (52.10±14.83 degrees). All the postures produced more than 1% maximum voluntary isometric contraction of the muscle (MVIC). The muscle activities of Tha Kae Siat Ook were the most contracted, whereas Tha Kae Lom Pat-Khat Kae Lom Nai Eo were the least. Moreover, the study found that the rectus femoris muscle was the most active muscle in all postures. In conclusion, this research can help to select the most appropriate Ruesi Dat Ton posture to maximize the benefits for practitioners and to ensure safety while performing the postures.